Profil Biokimia Darah Sapi Aceh pada Intensitas Estrus Yang Berbeda - Siregar, Tongku Nizwan; Prayogi, Agung; Jauhari, Jauhari; Meutia, Nellita; Yusmadi, Yusmadi; Melia, Juli; Panjaitan, Budi; Asmilia, Nuzul (Jurnal Veteriner; Vol 21 No 3 (2020), 2020)
Glucose, cholesterol, and protein are blood objects of macro-nutrients which are very important in gonadotropin synthesis. Gonadotropin secretion is closely related to estrous performance. This study aims to determine the biochemical profile of Aceh cattle blood during estrus with different estrus intensity. In this study, ten Aceh cattle were used with criteria aged 3-5 years, had at least one birth, had a normal reproductive cycle, healthy body condition, and had two regular estrus cycles. The blood biochemical profiles measured were total protein, cholesterol, and glucose levels. Spectrophotometer and Lab test reagent examined the samples. Data were analyzed using t test. The results showed that total protein content; cholesterol; and glucose at score 3 vs score 4 were 8.38 ± 0.84 vs 9.18 ± 2.77 g / dl (P> 0.05); 97.85 ± 22.21 vs 72.5 ± 3.37 mg / dl (P <0.05); and 2.22 ± 0.53 vs. 6.80 ± 5.87 (mg / dl) (P> 0.05), respectively. It was concluded that the difference in estrus intensity scores 3 and 4 of Aceh cattle was affected by cholesterol concentration, but not affected by total protein concentration and blood glucose.